2019
DOI: 10.1186/s12906-019-2786-z
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of traditional Japanese medicine Goshajinkigan in irradiation-induced aspermatogenesis in mice

Abstract: BackgroundInfertility and gonadal dysfunction are well known side-effects by cancer treatment in males. In particularly, chemotherapy and radiotherapy induced testicular damage, resulting in prolonged azoospermia. However, information regarding therapeutics to treat spermatogenesis disturbance after cancer treatment is scarce. Recently, we demonstrated that Goshajinkigan, a traditional Japanese medicine, can completely rescue severe busulfan-induced aspermatogenesis in mice. In this study, we aimed to detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…We also suggest that these medicines may act by reducing the testicular inflammation induced by BSF. We have previously demonstrated that impaired reproductive function induced by chemotherapy and radiotherapy was related to immune-pathophysiologies [17,31,32]. In the future, we propose to examine the effects of TJ7 and TJ41 alone or in combination on irradiation-induced spermatogenic defects and to further clarify their mechanisms of action, focusing on testicular immunology.…”
Section: Discussionmentioning
confidence: 98%
“…We also suggest that these medicines may act by reducing the testicular inflammation induced by BSF. We have previously demonstrated that impaired reproductive function induced by chemotherapy and radiotherapy was related to immune-pathophysiologies [17,31,32]. In the future, we propose to examine the effects of TJ7 and TJ41 alone or in combination on irradiation-induced spermatogenic defects and to further clarify their mechanisms of action, focusing on testicular immunology.…”
Section: Discussionmentioning
confidence: 98%
“…Gosha-Jink-Gan is a Kampo formula which is known to manage chemotherapy induced peripheral neuropathy [ 155 , 156 ]. Along with the study our research reviewed, it is newly receiving attention as a potential agent to recover spermatogenesis [ 93 , 157 ]. Saikokaryukatsuboreito is also another Kampo medicine, identified to improve spermatogenesis and testosterone levels [ 95 , 158 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that irradiation-mediated oxidative stress induces apoptosis primarily in adult mouse and rat germ cells [ 69 , 70 , 71 , 72 ]. Additionally, irradiation-induced germ cell apoptosis depends on activation of caspase-3 in three-month-old rats [ 72 ], concomitant with increased expression of caspase-8 and decreased expression of caspase-9 in adult rats and prepubertal mice, respectively [ 72 , 73 ] ( Table 1 , Figure 1 ). However, irradiation-induced apoptosis does not occur in all types of testicular somatic cells.…”
Section: Radiotherapymentioning
confidence: 99%
“…An increase in BTB permeability is known to enhance ASA production, resulting in infertility in males [ 85 , 86 , 98 ]. Recently, we reported that single-dose TBI induced ASA that preferentially reacted with mature spermatids and spermatozoa in prepubertal mice [ 73 ]. Our results showed that 6 Gy of TBI induced a disruption of spermatogenesis with a decrease in inter-Sertoli tight junction mRNA levels and the production of ASA ( Table 1 ).…”
Section: Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation